Enterprise risk management and economies of scale and scope: evidence from the German insurance industry - Altuntas, Muhammed; Berry-Stölzle, Thomas R.; Cummins, J. David (Annals of operations research, 2021)
Enterprise risk management (ERM) is the approach of managing all risks faced by an enterprise in an integrated, holistic fashion. This research investigates whether the utilization of the ERM approach helps firms achieve economies of scale and scope. We use detailed survey data of German property-liability insurance companies that allows us to construct continuous measures of ERM quality. We find that ERM quality positively moderates the size-scale efficiency relationship, and we find that ERM positively moderates the diversification-revenue scope efficiency relationship, indicating that ERM facilitates economies of scale and economies of scope with respect to revenue complementarities. We do not find any evidence of economies of scope with respect to cost complementarities. Our results suggest that ERM’s impact on economies of scale and scope is one answer to the question of how ERM can create value.